Cryptanalysis of RSA with Small Prime Difference. - De Weger, Benne
We show that choosing an RSA modulus with a small difference of its prime factors yields improvements on the small private exponent attacks of Wiener and Boneh-Durfee.
Keywords: Cryptanalysis; RSA; Fermat Factoring; Wiener Attack; Boneh-Durfee Attack